Exploring the feasibility of private micro flood insurance provision in Bangladesh - Akter, Sonia; Brouwer, Roy; Beukering, Pieter J.H. van; Laura, French; Silver, Efrath; Choudhury, Saria; Aziz, Syeda Salina (© 2011 Overseas Development Institute., 2016)
This article was published in Disasters [ © 2011 The Author(s) ] and the definite version is available at: https://doi.org/10.1111/j.1467-7717.2010.01218.x